Psoriatic epidermis is associated with upregulation of CDK2 and inhibition of CDK4 activity. (1st March 2020) - Henri, P.; Prevel, C.; Pellerano, M.; Lacotte, J.; Stoebner, P.E.; Morris, M.C.; Meunier, L.
Summary: Background: The cyclin‐dependent kinases (CDKs) CDK2 and CDK4 are involved in regulation of cell‐cycle progression, and psoriasis is characterized by hyperproliferation of basal epidermal cells. CDK inhibitory proteins (CKIs) such as p16 INK 4A (p16) bind CDK4/6 kinases and prevent their interaction with D‐type cyclins. CKIs such as p21 Cip1 (p21) and p27 Kip1 (p27) associate with CDK–cyclin complexes and prevent their activation. Objectives: To gain insight into the molecular implication of CDK2 and CDK4 kinases in psoriasis, we sought to characterize expression of these kinases and associated cyclins, as well as of CKIs, and addressed the status of CDK2 and CDK4 activity in human psoriatic epidermis. Methods: A cohort of 24 patients with psoriasis participated in the study. Biopsies were removed from a chronic plaque and from nonlesional skin. CDK2, CDK4, cyclin D1, cyclin E and CKI protein expression was assessed by immunoblotting, immunohistochemistry and immunofluorescence. CDK4 and CDK2 mRNA expression was determined by real‐time polymerase chain reaction. Specific kinase activities of CDK2 and CDK4 were evaluated using fluorescent peptide biosensors. Results: CDK2–cyclin E expression and activity were significantly increased in psoriatic epidermis compared with uninvolved adjacent skin. In contrast, CDK4–cyclin D1 activity was inhibited, although its expression was increased in psoriatic epidermis and its transcription slightly inhibited. p27 expression was reduced, while p16 and p21 expression was induced in psoriatic epidermis. Conclusions: Epidermal CDK2 activity is increased in psoriatic epidermis while CDK4 activity is completely inhibited. These alterations are not associated with changes in CDK transcription and instead involve post‐translational control mediated by decreased expression of p27 and p16 overexpression, respectively. What's already known about this topic? Cyclin‐dependent kinases (CDKs) are involved in cell‐cycle progression. The levels of cyclin partners and CDK inhibitors regulate their activity. Psoriasis is a chronic T‐cell‐driven inflammatory skin disease characterized by hyperproliferation of basal epidermal cells. What does this study add? Thanks to fluorescent peptide biosensors, this study demonstrates that epidermal CDK2 activity is increased in psoriatic epidermis while CDK4 activity is completely inhibited. These alterations involve post‐translational control mediated by decreased expression of p27, and p16 overexpression, respectively. What is the translational message? CDK2 and CDK4 are involved in regulation of cell‐cycle progression, and psoriasis is characterized by hyperproliferation of basal epidermal cells. Epidermal CDK2 activity is increased in psoriatic epidermis while CDK4 activity is completely inhibited. These alterations are not associated with changes in CDK transcription and instead involve post‐translational control mediated by decreased expression of p27 and p16 overexpression, respectively. Pharmacological modulation of CDK2 and CDK4 may constitute a promising therapeutic strategy.